Management and Support in Higher Education Ecosystems: Convergence of Psychological and Pedagogical Vectors in the Process of Distance Education - Barbashova, Iryna; et al., (European Journal of Social Science Education and Research, 2026)
Students’ mental health can be impacted by studying, academic pressure, institutional culture, and procedures; this is particularly true for distant learning. There are growing requests for universities to promote students’ well-being in a caring, all-encompassing manner and to recognize the obstacles posed by university cultures, structures, pedagogies, curricula, tuition, and assessment procedures. Our research, which is based on the integrative review method, shows that relationships with peers (e.g., sense of community and belonging), instructors (e.g., approachability, competence, sense of support), course design (e.g., content, delivery, assessment), and academic resources (e.g., learning materials, physical learning spaces) all have an impact on students’ well-being. This is a two-way relationship in which learning can be equally impacted by well-being. However, as research shows, the two domains – students’ wellbeing and academic performance – usually are considered separately, and for now the most innovative approach suggested by scholars and implemented by some HE facilities is embedding wellbeing disciplines into curriculum. Based on eco-system paradigm and conceptual modelling methodology, we suggested dynamic capabilities in university distance learning as digital ecosystem, with connectivity as one of the core elements. In higher education, connectedness and value co-creation are said to signify a change from considering students as passive learners to active participants in their education. In addition to improving learning results, this cooperative approach fosters a feeling of community and equips students for a changing workforce.
Keywords: students’ wellbeing, connectivity, digital ecosystem, value co-creation, knowledge sharing.